KONSEP ARSITEKTUR EKOLOGI PADA PERANCANGAN BUMI PERKEMAHAN PRAMUKA BOTUPINGGE DI GORONTALO - Nurcahyo, Bagas Dwi; Heryati, Heryati; Abdul, Nurnaningsih Nico (Universitas Negeri Gorontalo, 2024)
The Scout Movement is a scouting organization that is officially recognized by the government and is tasked with shaping the character of Indonesia's young generation. Kwartir Daerah Gorontalo (Kwarda Gorontalo) is a Scout Movement organization at the Gorontalo Province level which until now Kwarda Gorontalo is actively carrying out scouting activities and has hosted national camps, but Kwarda Gorontalo does not yet have a permanent camping ground. Therefore, it is necessary to design a Scout Campground in Gorontalo as an educational campus for Scout members.In the Scout Movement there are moral values related to the environment, namely love for nature and compassion for fellow human beings, if it is related to the field of Architecture, the science that studies the relationship between humans and nature, namely Ecological Architecture.The research method used in this design is descriptive qualitative method. Primary data collection was carried out by direct observation (observation), as well as interviews with related parties, while secondary data collection was carried out using literature study methods, book references, journals or theses, as well as through internet media. The result of the design is a complete campground building with facilities to support various kinds of scouting activities. The principles of ecological architecture in the form of minimizing land damage and minimizing energy use, are applied to the arrangement of the site and the shape of the building. The site is laid out by maintaining the existing potential, the shape of the building uses the principles of ecological architecture by applying a form that is in harmony with the Gorontalo traditional house and camping tents. Gerakan Pramuka merupakan organisasi kepanduan yang resmi diakui oleh pemerintah dan diberi tugas untuk membentuk karakter generasi kaum muda Indonesia. Kwartir Daerah Gorontalo (Kwarda Gorontalo) merupakan organisasi Gerakan Pramuka di tingkat Provinsi Gorontalo yang sampai saat ini Kwarda Gorontalo aktif melaksanakan kegiatan kepramukaan dan pernah menjadi tuan rumah perkemahan nasional, namun Kwarda Gorontalo belum memiliki Bumi Perkemahan tetap. Oleh sebab itu, diperlukan rancangan bumi perkemahan Pramuka di Gorontalo Sebagai kampus pendidikan anggota pramuka. Pada Gerakan Pramuka terdapat nilai-nilai moral yang berkaitan dengan lingkungan yakni cinta alam dan kasih sayang sesama manusia, jika dikaitkan pada bidang Arsitektur, ilmu yang mempelajari tentang hubungan manusia dan alam yakni Arsitektur Ekologi. Metode penelitian yang digunakan dalam perancangan ini adalah metode kualitatif deskriptif. Pengumpulan data primer dilakukan dengan cara pengamatan secara langsung (observasi), serta wawancara dengan pihak terkait, sementara itu pengumpulan data sekunder dilakukan dengan metode studi literatur, referensi buku, jurnal atau skripsi, serta melalui media internet. Hasil perancangan berupa bangunan bumi perkemahan yang lengkap dengan fasilitas untuk menunjang berbagai macam kegiatan kepramukaan. Prinsip-prinsip arsitektur ekologi berupa meminimalisir kerusakan lahan dan meminimalisir penggunaan energi, diterapkan pada penataan site dan bentuk bangunan. Site ditata dengan mempertahankan potensi yang ada, bentuk bangunan menggunakan prinsip-prinsip arsitektur ekologi dengan menerapkan bentuk yang selaras dengan rumah adat Gorontalo dan tenda perkemahan.